Case Report: Para-infectious cranial nerve palsy after bacterial meningitis - Zanotelli, Giovanni; Bresciani, Lorenzo; Anglani, Mariagiulia; Miscioscia, Alessandro; Rinaldi, Francesca; Puthenparampil, Marco (Frontiers in Immunology, 2022)
A 27-year-old woman was admitted to our hospital for fever, associated with headache, nausea, and vomiting, and she rapidly developed mild left facial nerve palsy and diplopia. Neurological examination revealed mild meningitis associated with bilateral VI cranial nerve palsy and mild left facial palsy. As central nervous system (CNS) infection was suspected, a diagnostic lumbar puncture was performed, which revealed 1,677 cells/μl, 70% of which were polymorphonuclear leukocytes. Moreover, multiplex PCR immunoassay was positive for Neisseria meningitidis, supporting the diagnosis of bacterial meningitis. Finally, IgG oligoclonal bands (IgGOB) were absent in serum and cerebrospinal fluid (CSF). Therefore, ceftriaxone antibiotic therapy was started, and in the following days, the patient’s signs and symptoms improved, with complete remission of diplopia and meningeal signs within a week. On the contrary, left facial nerve palsy progressively worsened into a severe bilateral deficit. A second lumbar puncture was therefore performed: the CSF analysis revealed a remarkable decrease of pleocytosis with a qualitative modification (only lymphocytes), and oligoclonal IgG bands were present. A new brain MRI was performed, showing a bilateral gadolinium enhancement of the intrameatal VII and VIII cranial nerves bilaterally. Due to suspicion of para-infectious etiology, the patient was treated with oral steroid (prednisolone 1 mg/kg/day), with a progressive and complete regression of the symptoms. We suggest that in this case, after a pathogen-driven immunological response (characterized by relevant CSF mixed pleocytosis and no evidence of IgGOB), a para-infectious adaptive immunity-driven reaction (with mild lymphocyte pleocytosis and pattern III IgGOB) against VII and VIII cranial nerves started. Indeed, steroid administration caused a rapid and complete restoration of cranial nerve function.